A Note on Addition to the Flora of Banswara District in Rajasthan - Singh, G.; Rathod, T. R.; Baloch, S. R.; Purohit, Chandan Singh (Indian Forester, 2008)
During study on vegetation diversity, 88 species of grasses and herbs were identified in 2005 and 2006 at Bara Nandara kho, Banswara (Rajasthan). Out of these, 14 species recorded as new arrival in the areas, when compared with the other existing literature of the region. These species are Brachiaria deflexa, Brachiaria setigera, Croton bonplandianum, Cyperus arenarius, Eragrostis aspera, Euphorbia granulata, Indigofera sessiliflora, Justicia prostrata, Justicia simplex, Ocimum canum, Rhynchosia bracteata, Sporobolus nervosus, Stylosanthes fruticosa and Triumfetta rhomboidea. Out of these B. deflexa, B. setigera and C. arenarius are species of xeric environment; whereas the other species are of semi-arid or dry sub-humid region. Such changes in vegetation composition resulted from invasion of other species are indicative of variations in climatic and edaphic conditions in the region.